Cardiorespiratory Fitness Cut-Points Related to Body Adiposity Parameters in Macedonian Children - Elezi, Abdulla; Kadriu, Valon; Elezi, Gresa; Georgiev, Georgi; Gontarev, Seryozha (LLC OVS, 2022)
Background and Objectives: There is a shortage of criteria referent standards for tests of logistic application meant to estimate the cardiorespiratory fitness (CRF) of children and adolescents in the Republic of North Macedonia. The goal of the research was twofold: (1) To identify the ability of CRF estimated by the 20-m shuttle-run test (20mSRT) to discriminate between “healthy” and “unhealthy” phenotypes (by adiposity measures such as WC and WHR) in children; (2) To determine the correlation between obesity and relatively maximum oxygen consumption (VO2 peak) tested on a relatively large respondents’ sample of Macedonian children. The research was conducted on a sample of 1,863 respondents, 957 (51.4%) of whom were boys, and 906 (48.6%) were girls at the age of 7 to 10 years. All of them were from 19 primary schools in the central and eastern parts of the Republic of North Macedonia.  Materials and Methods: The waist circumference (WC) and waist-to-height ratio (WHtR) were used to identify body adiposity markers. CRF was measured using the 20mSRT (VO2 peak). Receiver operating characteristic curves and logistic regression were applied in order to establish the discriminative power of CRF in anticipating the parameters of body adiposity markers.  Results: With regard both to the boys and girls, VO2 peak showed considerable predictive power of identifying the body adiposity (area under the curve [AUC] > 0.66). In boys, when considering the full sample (7-10 years), the best cut-point for VO2 peak to detect body fat by WC were 48.8 to mL•kg−1•min−1 and WHtR were 47.4 to mL•kg−1•min−1. For girls, when considering the full sample (7-10 years), the best cut-point to detect body fat by WC were 47.4 to mL•kg−1•min−1 and WHtR were 47.1 to mL•kg−1•min−1.  Conclusions: According to these cut-points, adolescents with low CRF were more likely to be obese either by WC or WHtR. The border values (cut-points) of CRF can be used as quantitative markers of children of healthier body characteristics from the Republic of North Macedonia.